Russia-Ukraine balance of military power - Jokull Johannesson (Journal of International Studies)
The Russia-Ukraine conflict is the most serious test of European security in the 21st century and the forgone conclusion is that Russia can easily prevail in the conflict, but this has not been the case. This article uses balance of military power analysis to report findings on the plausible outcome of a war between Ukraine and Russia. I report findings based on realist theoretical perspectives that indicate Russian victory is unlikely because of relative balance of power where Russia has to face multiple threats diverting its military power while Ukraine can concentrate its military power for a single purpose. The findings suggest implication for policy in Russia, Ukraine, EU and the United States of America.